Morphofunctional properties of a differentiated Caco2/HT-29 co-culture as an in vitro model of human intestinal epithelium. Issue 2 (27th April 2018) - Ferraretto, Anita; Bottani, Michela; De Luca, Paola; Cornaghi, Laura; Arnaboldi, Francesca; Maggioni, Margherita; Fiorilli, Amelia; Donetti, Elena
Abstract : An intestinal 70/30 Caco2/HT-29 co-culture was set up starting from the parental populations of differentiated cells to mimic the human intestinal epithelium. Co-culture was harvested at confluence 0 (T0) and at 3, 6, 10, and 14 days post confluence after plating (T3, T6, T10, and T14, respectively) for morphological and functional analysis. Transmission electron microscopy revealed different features from T0 to T14: microvilli and a complete junctional apparatus from T6, mucus granules from T3, as also confirmed by PAS/Alcian Blue staining. The specific activity of alkaline phosphatase (ALP), aminopeptidase N (APN), and dipeptidyl peptidase IV (DPPIV) progressively increased after T0, indicating the acquirement of a differentiated and digestive phenotype. Transepithelial electrical resistance (TEER), indicative of the barrier properties of the monolayer, increased from T0 up to T6 reaching values very similar to the human small intestine. The apparent permeability coefficient for Lucifer Yellow (LY), along with morphological analysis, reveals a good status of the tight junctions. At T14, HT-29 cells reduced to 18.4% and formed domes, indicative of transepithelial transport of nutrients. This Caco2/HT-29 co-culture could be considered a versatile and suitable in vitro model of human intestinal epithelium for the presence of more than one prevalent intestinal cell type, by means of a minimum of 6 to a maximum of 14 post-confluence days obtained without the need of particular inducers of subclones and growth support to reach an intestinal differentiated phenotype.